2016
DOI: 10.1016/j.appet.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Picky eating in preschool children: Associations with dietary fibre intakes and stool hardness

Abstract: It has been suggested that constipation may be associated with picky eating. Constipation is a common condition in childhood and a low intake of dietary fibre may be a risk factor. Differences in fibre intake between picky and non-picky children and its relation to stool consistency is currently not well-understood. Children enrolled in the Avon Longitudinal Study of Parents and Children identified as picky eaters (PE) were compared with non-picky eaters (NPE): (1) to determine dietary fibre intake at 38 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 39 publications
3
37
1
3
Order By: Relevance
“…Although girls who were persistent picky eaters reported even lower intakes of vegetables, differences between groups were marginal. These findings are in agreement with those from the NHANES in this age group and with those from previous studies (10,11,24). Overall, persistent picky eating was associated with problems in food intake that were similar to the national trends in children and adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…Although girls who were persistent picky eaters reported even lower intakes of vegetables, differences between groups were marginal. These findings are in agreement with those from the NHANES in this age group and with those from previous studies (10,11,24). Overall, persistent picky eating was associated with problems in food intake that were similar to the national trends in children and adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…Picky eating was also associated with an increase in the odds of having hard stools of about 30%, and this relationship was mediated by dietary fibre. (40) Dietary fibre intake in children who were not picky eaters was 9.1 g NSP fibre/day (about 11 g AOAC fibre/day), which is below the UK Scientific Advisory Committee on Nutrition (SACN) guideline of 15 g AOAC fibre/day for children aged 2-5 years old (66) . The even lower intake of the picky eaters was largely a consequence of a lower intake of vegetables and fruit than the non-picky eaters.…”
Section: Health and Developmentmentioning
confidence: 84%
“…van der Horst et al (14); Dubois et al (17) ), food frequency questionnaires (FFQ) (e.g. Taylor et al (40); Antoniou et al (44) ), 2-, 3-or 4-day food diaries (e.g. Taylor et al (22); Rohde et al (42) ), and combinations of methods (45; 46) , as well as alternative methods such as recording food selection from a pre-stocked chiller box (27) .…”
Section: Diet: Nutrients Food Groups/foods and Diversitymentioning
confidence: 99%
“…The amount of DF which would be considered adequate for constipated children is unknown, but certainly it should not be lower than for healthy children (perhaps somewhat higher, instead), taking into account that most studies depicted a lower DF intake in constipated than in control children and, therefore, low DF intake is considered a risk factor for FC (4,23,42) . It was also shown that adherence to a 'Health Conscious' dietary pattern was associated with a lower prevalence of constipation at 24 months of age (43) , that there could be a bidirectional association between fussy eating and functional constipation in preschool children (44) and that picky eating was associated with a lower DF intake and hard stools (45) .…”
Section: Treatmentmentioning
confidence: 99%